NILAI-NILAI RUMAH TANGGA DALAM NOVEL-NOVEL AHMAD TOHARI: TRILOGI RONGGENG DUKUH PARUK, BEKISAR MERAH DAN BELANTIK - Mugijatna, Mugijatna (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2011)
This study is cunducted to discuss the problem of householdÂ values in Ahmad Tohariâ€™s novels: Ronggeng Dukuh Paruk trilogy, Bekisar Merah and Belantik (Bekisar Merah II). As for the purpose is to describe household values in the novels,Â to describe Ahmad Tohariâ€™s intention to reveal household values inÂ the novels, and to describe the significance of household values in the novels. This study uses cultural approach with hermeneutics as its methodology and semiotics as its analysis. The findings are, first, household values in Ronggeng Dukuh Paruk trilogy is expressed in a form of Rasusâ€™ refusal toward pornographic ronggeng tradition and Srintilâ€™s struggle to become domestic woman. In Bekisar Merah and Belantik, it is expressed in a form of Kanjatâ€™s attitude to marry Lasi honorably and Lasiâ€™s refusal to have sexual intercourse outside marriage. Second, Ahmad Tohariâ€™s intention to express household values inÂ the novels isÂ to develop civilization which is clean from immorality.Â Third, the significance of household values in the novels is as â€™model ofâ€ inherited values, at the same time as â€™model forâ€™ struggle to continue the inherited values. Besides that, the values also have a significance ofÂ â€a candle in darknessâ€ to face tradition which nurture sexual intercourse outside marriage andÂ the promulgation of sexual intercourse outsideÂ marriage by hedonistic life.